2022
DOI: 10.3390/tomography8050205
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Biochemical Recurrence Resulted Negative on [68Ga]Ga-PSMA-11 but Positive on [18F]Fluoromethylcholine PET/CT

Abstract: For prostate cancer (PCa) biochemical recurrence (BCR), the primarily suggested imaging technique by the European Association of Urology (EAU) guidelines is prostate-specific membrane antigen (PSMA) positron emission tomography/computer tomography (PET/CT). Indeed, the increased detection rate of PSMA PET/CT for early BCR has led to a fast and wide acceptance of this novel technology. However, PCa is a very heterogeneous disease, not always easily assessable with the highly specific PSMA PET with around 10% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…However, it should be acknowledged that most of the PSMA PET data are based on retrospective series, and the high cost and limited availability of this method are still major limitations ( 15 ). Therefore, taking into account also the heterogeneity of the disease and that almost 10% of PCa is PSMA negative, we believe that choline PET/CT still represents an effective molecular imaging technique that should be considered ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be acknowledged that most of the PSMA PET data are based on retrospective series, and the high cost and limited availability of this method are still major limitations ( 15 ). Therefore, taking into account also the heterogeneity of the disease and that almost 10% of PCa is PSMA negative, we believe that choline PET/CT still represents an effective molecular imaging technique that should be considered ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, as highlighted by immunohistochemistry studies, it is now known that there is a heterogenous PSMA expression in both primary tumors and distant metastasis [ 14 ]. Furthermore, around 10% of cases occur with low or without PSMA expression [ 15 , 16 , 17 ]. Interestingly, in these studies, most of the patients with low/absent PSMA expression showed infiltrative growth patterns.…”
Section: Introductionmentioning
confidence: 99%
“…However, the diagnostic accuracy of PSMA PET is challenged by findings that claim that up to 15% of clinically relevant PCa cases do not express this protein [ 8 ], leading to false negative results. Moreover, further cancer de-differentiation in the metastatic castration-resistant (mCR) late stages of the disease increases this percentage [ 9 , 10 ]. Therefore, identifying alternative imaging biomarkers that complement PSMA PET in such clinical circumstances represents an unmet clinical need.…”
Section: Introductionmentioning
confidence: 99%